The Rapport of Health Education Through Brainstorming Methods on Students' Knowledge and Attitudes About Sexuality Issues at the State Junior High School Darussalam District Banda Aceh - Desreza, Nanda; Muntaza, Anjana; Sartika, Dewi (PHARMACOLOGY, MEDICAL REPORTS, ORTHOPEDIC, AND ILLNESS DETAILS, 2025)
Sexual conduct is an activity motivated by sexual desire. Teenagers' attitudes will be influenced by their lack of understanding about premarital sex. Brainstorming approaches can also be used to address problems based on the ideas presented by pupils. The purpose of this study was to determine students' knowledge and attitudes toward sexuality issues before and after giving health education using the brainstorming approach at the State Junior High School 8 Darussalam district Banda Aceh. This investigation was a quasi-experiment. Data was collected from March 7 to April 6, 2023. This study used a sample of 15 brainstorming groups from State Junior High School. Data was collected via primary sources. The Wilcoxon test was employed in the analysis, which included univariate and bivariate approaches. The findings revealed variations in knowledge (p-value 0.001) and attitudes (p-value 0.001) among the brainstorming groups. The researchers determined that brainstorming had a considerable impact on pupils' knowledge and attitudes.